Upaya Meningkatkan Aktifitas Belajar Siswa dengan Menggunakan Model Pembelajaran Tipe Students Teams Achievements Devision (STAD) pada Mata Pelajaran IPA - Alizar Alizar (JPGI (Jurnal Penelitian Guru Indonesia), 2016)
This research aims to know about students’ activities by using teams of students’ learning model type achievements devision (STAD) at IX.3 Grade of IPA Subjects in SMPN 1 Nan Sabaris. The type of STAD can Implement of Model Cooperative Learning, cooperative centered learning, the students can build and improve their knowledge in seeking settlement of a matter must be understood and controlled, either individually or in groups. In addition, teacher’s act motivator and facilitator (2). By using STAD Learning Model to improve student learning activities lesson in class IX.3 IPA at SMPN 1 Nan Sabaris. (3). Using Learning science STAD type of cooperative learning model can improve student learning outcomes IX.3 grade SMP N 1 Nan Sabaris. However, learning outcomes of students from the first cycle to the second cycle increased by 16.17%, it can be seen from the average value obtained in the first cycle is 64 and increased in the second cycle into 80.17 this is evidence of the implementation of the research that has been done in  SMP N 1 Nan Sabaris have been successful. In addition, the STAD cooperative learning not only increases cognitive learning outcomes alone but also affective and psychomotor.